Application of element decomposing method for solving integer problems - Ekkaphon Jaiyen (2018)
© The Authors, published by EDP Sciences, 2018. This research objective is to solve the integer problems by using an algorithm that applied to the element decomposing method (EDCM). Integer problem is a NP-hard when the problem is large-size, more time needed to solve the problem. The EDCM cuts a structure into several elements and reconnects elements at "nodes". This process can disconnect other nodes that not connected with the element. Moreover, it appropriately need in optimization solutions for applications, in which can give answers faster by cutting the nodes in finding the answers. There's 2 phases of step on this research. The first phase is input data and simplex method, while the second phase is creating and developing the algorithm from EDCM application. The comparison results show how two methods are carried out between EDCM and B&B Method. The results from two methods are focused on the value and solution step by step. According to the problem, it can be solved within the number of variables 2-15. The value of the difference in the answer is on average at 0.00% and solution step used for solving problem is less on average at 40.89 %.